The cognitive effects of long term imprisonment - Banister, P. A. (1978)
This thesis presents data on the psychological correlates of long term imprisonment for a representative sample of men serving either indeterminate or determinate sentences of ten years or over in a number of English prisons. Four groups of prisoners matched for age but differing in mean length of total imprisonment served were tested on a battery of cognitive tests, comprising tests of reaction time, the Gibson Spiral Maze, the General Aptitude Test Battery Form Matching subtest, the Wechsler Memory Scale Associate Learning and Visual Reproduction subtests, the Purdue Pegboard and the Wechsler Adult Intelligence Scale. The 154 men left from the initial sample of 175 prisoners after a mean interval of 19.08 months were retested, thus permitting two cross-sectional analyses and a longitudinal analysis of the results. The results indicated no straightforward relationship between test performance and length of imprisonment; there was no decline in general intellectual capacity, but there was a reduction in perceptual-motor speed. In addition, there was evidence of an increased reliance on verbal skills. These results were discussed in relation to showing similarities to those derived from studies of ageing. A number of possible moderating variables which could provide alternative explanations for the results found were also investigated, and it was found that the results could not be accounted for in terms of differential release on parole, differential use of prison educational or other facilities, or differences between the groups in terms of their offence category or criminal history. The quantitative approach used in this study was also critically analysed, and compared to an alternative qualitative approach to the same area, it being concluded that both methods were of use in the study of the effects of long term imprisonment